การออกแบบและพัฒนาระบบงานผลิตรายการโทรทัศน์ - มุนินทร์ ชูฉัฏฐะ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this research was applied for analysis, design and develop system of television program production. Television operators can take the result of information report after analysis by this program to help them of perform move convenience and effective than currently. This program system will reduce time to arrange schedule of television program, database recording and database finding such as, television program, name of customers, local producers and foreign producers and concern television program production. This program system can analysis schedule of television program such as, ever time is each day, double programs in same time, and additional of special program than effect to broadcast schedule, quickly print out the changing data to customer and concern section. And this program system can support television operator perform easier and more convenience. And then can reduce investment for manpower. This research used data of the Mass Communication Organization of Thailand (MCOT), apply to this research. Designing was used according to relational database, computer structure method and decision problem by use sequence and weight when have changing of broadcast schedule. This program system used Visual Basic program. The structure of this program compose of sections, (1) Section of program (2) Section of television production, (3) Section of art and designing, (4) Section of article, (5) Section of administration. There are 49 window screens and 23 reports. The management for free time, we used fundamental concept base on management of program schedule and perform sequence by uses whether program that has shortest time or used waste tiem after broadcast. The result of this research, after television operators used this program system in all 5 sections. We found that television operators performed easier and more convenience for television for television program production. We can reduce time when compare with last time that we calculate on paper worksheet and print out the report by computer. Anyway in case of special program, we can display information that was changed for any decision such as cancel program, reduce broadcast time or switch program. Than offer information/report to supervisor for final decision